Cross-Border M&A and High-End Brand Transformation: A Case Study of ANTA’ s Acquisition of Amer Sports - Zhang, Yusong (Asia Pacific Economic and Management Review, 2026)
With the deepening of global economic integration, cross-border mergers and acquisitions (M&A) have become a vital strategy for Chinese enterprises to achieve high-end brand transformation. This paper examines the leveraged acquisition of Amer Sports by a consortium led by ANTA Sports, a landmark transaction valued at 4.6 billion euros. Through case analysis and financial data verification, the motivations, risks, and integration strategies of this deal are systematically explored. The research indicates that the primary motivations include expanding global market share, optimizing the brand portfolio to move up the value chain, and seizing growth opportunities in the Chinese winter sports market. Despite challenges such as high financial leverage and cross-cultural integration issues, ANTA successfully achieved synergies. This was achieved by maintaining brand independence, empowering backend operations, and promoting a direct-to-consumer (DTC) model. Financial data reveals that Amer Sports achieved profitability in 2021, with revenue reaching 5.18 billion USD by 2024. This case provides significant insights for Chinese consumer goods companies seeking to expand internationally through strategic acquisitions.